Public Engagement Impact on Sustainable Waste Management in Indonesia: Examining Public Behavior - Salsabila, Lubna; Teovani Lodan, Karol; Khairina, Etika (Jurnal Administrasi Publik (Public Administration Journal), 2023)
The primary objective of this study is to investigate the behavioral patterns and levels of public engagement in waste management practices within the context of Indonesia. The issue of waste management is a significant and unresolved one that continues to be prioritized by the government. The issue of waste management has received much scholarly attention over the past twenty years. The prioritization of solid waste management is necessary to effectively attain the Sustainable Development Goals (SDGs). The present state of excessive garbage accumulation is a significant concern, with a substantial portion of it remaining unattended. The presence of hazardous elements within solid waste presents a significant risk to human life, both in the immediate and long-term. One factor contributing to the limited engagement of the public in environmental policy is the inclination of individuals to prioritize legislation primarily concerning their fundamental needs. This finding suggests a deviation from the outcomes of other research undertaken in recent decades, which posit that community engagement plays a major role in addressing waste management challenges. The findings of the study indicate that individuals' behavior has a significant role in shaping their inclination toward participating in trash management initiatives throughout various urban areas in Indonesia.